2013
DOI: 10.1590/s2176-94512013000500012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chin advancement surgery in hyoid bone and tongue positions and in the dimension of the oropharynx

Abstract: The oropharyngeal dimension increased as the tongue base and hyoid bone were repositioned more anteriorly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…This bone plays a significant role in physiological functions such as ingestion, respiration and speaking. Researchers have shown that changes of mandibular position are pertinent to the hyoid bone alterations, and the hyoid bone position adapts to antero-posterior changes of the head ( 10 - 12 ). Also, adaptation of hyoid bone position after orthognathic operations has been revealed ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…This bone plays a significant role in physiological functions such as ingestion, respiration and speaking. Researchers have shown that changes of mandibular position are pertinent to the hyoid bone alterations, and the hyoid bone position adapts to antero-posterior changes of the head ( 10 - 12 ). Also, adaptation of hyoid bone position after orthognathic operations has been revealed ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…The cephalometric analyses were performed digitally by means of the Radiocef Studio 2 program (Radiomemory Ltda, MG, Brazil), using a resolution of 300 dpi for the teleradiographs [ 9 ]. For this purpose, the radiographs were digitized by a table scanner (Cranex D ® Soredex Orion Corporation, Tuusula, Finland) [ 10 ], coupled to a transparency reader, using a resolution of 300 dpi, and saved in TIFF format ( Tagged Image File Format ) without compression.…”
Section: Methodsmentioning
confidence: 99%